REDESIGNING MEDICAL STUDENTS' TRAINING THROUGH VIRTUAL CLINICAL SIMULATION (Proceedings of the International Conference on Education, 2021)
Clinical simulation is an engaging teaching strategy that has been used to develop disciplinary and soft skills in medical students through structured educational activities with assessment and feedback. COVID-19 has forced medical schools into redesigning many curricular activities, including these clinical simulations, which leveraged virtual technologies to continue the training amid the pandemic. The objective of this study was to assess the adaptation of clinical simulation to a virtual-based format to continue medical students' training. The sample of participants in this study was 34-third-year medical students. Simulation sessions were held through a synchronous videoconference platform where students used a monitor for vital signs, an actor simulated a patient, and the corresponding lab results and imaging studies were available upon students' request. Students provided care for the patient by teams; they interviewed and asked for physical exam findings from an actor representing a nurse. The simulation adapted to the team's performance, students were provided with the test results as they requested, and the patient's vital signs responded to the team's prescriptions. Following the simulation, they received feedback using the debriefing with a good-judgment framework which supports a reflection regarding their mental processes leading to decision-making.  Adapting educational strategies using technology in remote teaching is essential for medical schools to continue their training. This curricular adaptation exemplifies a proficient way to carry out virtual simulation activities amid the pandemic, easily adapted to other disciplines and educational levels.
Keywords: higher education, educational innovation, professional education, pandemic adaptations, COVID-19, virtual simulation